Artificial life and intelligent agents : second international symposium, ALIA 2016, Birmingham, UK, June 14-15, 2016, revised selected papers /: second international symposium, ALIA 2016, Birmingham, UK, June 14-15, 2016, revised selected papers. ([2018]) - Unknown
No abstract available